Problems of the effectiveness of the implementation of international agreements in the field of waste management: the study of the experience of Kazakhstan in the context of the applicability of European legal practices - Zhamiyeva, R.; Sultanbekova, G.; Balgimbekova, G.; Mussin, K.; Abzalbekova, M.; Kozhanov, M. (My University, 2021)
The issue of developing effective legal regulation of waste management and implementation of best practices in this area is relevant for many countries of the world. In the Republic of Kazakhstan, the development of a regulatory framework for waste management is still in its infancy. This situation poses a potential threat to the environment and public health. The question of this study is what are the obstacles to the effective implementation of international agreements in the field of waste management in Kazakhstan? What international legal instruments in the field of waste management are not fully used and what legislative initiatives need to be implemented in this regard? In order to assess the applicability of their regulations to the conditions of Kazakh law, the study examines such supranational legal instruments as, in particular, the Basel Convention on the Control of Transboundary Movements of hazardous wastes and their disposal, the Espoo Convention, Directive (EU) 2018/852 of the European Parliament and of the Council. As this study suggests, an impending problem for Kazakhstan is the issue of utilization of WEEE and the implementation of the Basel Convention regarding the issue of transportation and disposal of WEEE. Despite the growing interest in the issues of proper waste management, mechanisms related to the implementation of the Espoo Convention and the Aarhus Convention are poorly implemented in Kazakhstan. This study uses the method of political and legal analysis, with the help of which it examines the problems of the effectiveness of the implementation of international agreements in the field of waste management in the Republic of Kazakhstan and ways to overcome them. To achieve these goals, international legislative acts in the field of environmental protection and the legislation of the European Union and EU member states were analyzed, which made it possible to determine the possibility of applying foreign practices on legal regulation of waste management and implementation of international legal acts mechanisms in Kazakhstan. The study attempts to give a qualitative assessment of the elaboration of the legislative regulation of the waste management sphere in Kazakhstan. The solution of problems in the field of waste management at the state level can be feasible only with a systemic rather than partial reform of the legal framework. Based on the EU practices in the implementation of international and supranational environmental agreements, the optimal combination of state and market instruments would improve the regulatory framework of Kazakhstan in the field of waste management. In order to create the most beneficial effect in countering the accumulation of waste without harming the economy, it would be useful to apply proactive and preventive approaches to increase the responsibility and participation of all stakeholder groups.
Keywords: Environmental legislation; Environmental management; Legislative regulation of waste management; Life cycle assessment; Waste management; Zero waste